Analisis Komponensial Makna Preposisi Lokatif Bahasa Arab: Sebuah Penulusuran Awal / Componential Analysis of Arabic Locative Preposition: An Initial Study - Azis Zulfian Adisianto; Mohammad Masrukhi (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
This research discusses componential analysis of the meaning of Arabic locative prepositions. Prepositions in Arabic have their own uniqueness in terms of meaning, the seven locative prepositions in Arabic, namely fī, min, li, bi, 'an, ilā, 'alā are known to have synonymous meanings and can replace each other, this creates confusion for students, especially non-native Arabic from Indonesia. Therefore, this research focuses on studying the identification of meaning components of seven synonymous locative prepositions using a componential analysis of meaning approach through the use of Arabic fusḥā from various sources using the corpus method in order to determine the differences in meaning components between locative prepositions. This research produces findings on differences in the levels of meaning components of location, direction, distance, and characteristics of preposition objects including animate-inanimate and static-dynamic. It is concluded that all locative prepositions can be used to express location in a static third dimension, but there are specific differences regarding the meaning components. In other words, even though they are synonymous, the seven prepositions have more detailed differences when viewed in terms of components. So that Arabic language learners can use these locative prepositions according to the context and situation.Abstrak: Penelitian ini membahas mengenai analisis komponensial makna preposisi lokatif dalam bahasa Arab. Preposisi dalam bahasa Arab memiliki keunikan tersendiri dari segi makna, tujuh preposisi lokatif dalam bahasa Arab yaitu fī, min, li, bi, ’an, ilā, ’alā diketahui memiliki makna yang bersinonim dan dapat saling menggantikan, hal ini menghasilkan kebingungan tersendiri bagi pemelajar bahasa Arab non-native dari Indonesia. Oleh karena itu, penelitian ini fokus mempelajari identifikasi komponen makna tujuh preposisi lokatif yang bersinonim dengan menggunakan pendekatan analisis komponensial makna melalui penggunaan bahasa Arab fusḥā dari berbagai sumber dengan menggunakan metode korpus agar mengetahui perbedaan komponen makna antar preposisi lokatif. Penelitian ini menghasilkan temuan pada perbedaan ataran komponen makna letak, arah, jarak, dan karakteristik objek preposisi meliputi bernyawa-takbernyawa dan statis-dinamis. Semua preposisi lokatif tersebut dapat digunakan untuk menyatakan lokasi pada dimensi tiga yang statis, tetapi ada perbedaan-perbedaan spesifik mengenai komponen makna tersebut. Dengan kata lain, meskipun bersinonim, ketujuh preposisi tersebut memiliki perbedaan lebih rinci jika ditinjau dari segi komponen. Sehingga pemelajar bahasa Arab dapat menggunakan preposisi lokatif tersebut sesuai konteks dan situasinya.